Impact of Cotton Development Programme on Adoption of Recommended Bt Cotton Cultivation Practices (Indian Journal of Extension Education, 2022)
The study assessed the impact of Cotton Development Programme (CDP) on the adoption of recommended management practices in Bt-cotton (Gossypium hirsutum L). The data was collected from 210 farmers over a period of six years to make quantitative comparison with baseline data collected during the initial three year period (2013-15) from Mansa district of Punjab. The adoption of crop management practices in Bt-cotton in terms of recommended Bt-cotton hybrids, seed rate, fertilizer dose, use pattern of potassium nitrate (KNO3; 13:00:45) and reduction in insecticide use was investigated to quantify the impact of the CDP in the study region. These results revealed that area under recommended Bt cotton hybrids increased from a meager 15.2 per cent to as high as 89 per cent; adoption of recommended use nitrogenous fertilizers increased by 15.1 per cent; and the productivity of Bt-cotton enhanced by 138 per cent during this period. Therefore, it could be concluded that implementation of CDP was successful in the revival of Bt-cotton cultivation which was severely affected due to severe attack of sucking pests particularly by whitefly (Bemisia tabaci) during kharif-2015.